KNOWLEDGE AND PRACTICES OF MEDICAL STAFF TOWARD FUNGAL INFECTION PREVENTION FOR MEDICINAL PLANTS AT SOME HOSPITALS IN NGHE AN PROVINCE, AND INTERVENTION EFFECTIVENESS, 2019 (Vietnam Journal of Community Medicine, 2022)
Objectives: This study was conducted with the aim of evaluating the knowledge, attitudes, and practices of medical staff toward fungal infection prevention for medicinal plants, and interventional effectiveness at some hospitals in Nghe An province in 2019.Materials and methods: Employed methods are descriptive and intervention approaches. A total of 60 medical staff in 10 hospitals doing traditional medicine were included for the study.Results: From 80.0% to 100.0% of the respondents had a correct understanding of the causes of fungal infection in medicinal plants including high temperature, high humidity, poor ventilation, poor lighting, unperiodic checking and drying, and lack of storage facilities. 95% of the respondents knew that use of medicinal plants infected with fungi would cause diseases. 85% were aware that fungal diseases are transmitted through eating and drinking. Only 25% of the staff could name some fungi in medicinal plants, and none of them knew that medicine plants need daily checking.Communication intervention had a huge impact on the knowledge of the medical staff. Specifically, those who knew at least one fungal species increased from 25.0% to 100%, the effectiveness reached 300.0%. Those who knew the maximum allowable temperature in the medicine store of < 30°C rose up from 66.67% to 100.0%, the effectiveness reached 50.0%. Those who knew the allowable humidity in the store of < 70% jumped from 50.0% to 100.0%, the effectiveness reached 100.0%. Those who knew the wind speed < 0.5 m/s went up from 10.0% to 100.0%, the effectiveness reached 900.0%. Thus, fungal infections in medicinal plants at the four hospitals decreased by 50.00% to 72.73%.Conclusion: The knowledge and practices of medical staff toward fungal prevention for medicinal plants was limited.
Keywords: Fungi, herbal medicine, knowledge, practices.